(untitled) (UNED Research Journal, 2018)
On a global scale, agriculture is considered the most vulnerable to drought, representing one of the most devastating climate threats. For this reason, the objective of this work was to analyze the occurrence of meteorological drought by means of time series of the Normalized Precipitation Index during the period (1980-2014) for four Venezuelan agricultural sites. For the analysis, we used the combination of two multivariate methods: the Principal Coordinate Analysis of the data matrices using Euclidean Distance and the Cluster Analysis. The results of the analysis revealed three groups of years for the localities El Tigre and Banco de San Pedro, represented by the wet years, normal or intermediate conditions and years with significant water deficit; while for the rest of the localities (Tapipa-Padrón and El Guayabo) only two groups of years are distinguished (humid and dry). The statistical methodology based on the multivariate analysis allowed delineating groups of years that showed similar patterns of the index of meteorological drought as a function of the time series. The study is the backbone for space planning and the strengthening of strategies for food security in those localities.